Meningkatkan kemandirian toilet training anak dengan Global Developmental Delay - Najwa Wafiyyah (Universitas Muhammadiyah Malang, 2023)
Each level of age in humans will have certain developments. Likewise, at the age level of children, there will be abilities that will increase as they get older. Children aged 4-5 years have started to have the ability to apply self-help skills to meet their basic needs such as food, clothing, grooming, personal hygiene and independence in going to the toilet. The client is the youngest daughter of 2 siblings. Children with global developmental delay problems will have difficulties in self-care. He is 4 years old. The client lives with his parents, brother and grandmother. Until now the client has not been able to behave independently of his daily activities such as going to the toilet himself. The purpose of this case study is to improve the subject's ability to be independent with toilet training. The assessments used were observation, interviews and VSMS (Vineland Social Maturity Scale). The intervention given to improve the toilet training ability of the client was the provision of positive reinforcement. The results of the intervention that had been given to the client showed significant changes, namely a decrease in the intensity of bed wetting and an increase in the ability to take off/put on pants, wash, flush and wash hands independently. However, clients still need family assistance in going to the toilet or must remain with parental assistance and initiative. Setiap tingkatan usia pada manusia akan memiliki perkembangan tertentu. Demikian pula pada tingkat usia anak-anak, akan ada kemampuan yang akan meningkat seiring bertambahnya usia. Anak usia 4-5 tahun sudah mulai memiliki kemampuan untuk menerapkan keterampilan menolong diri sendiri untuk memenuhi kebutuhan dasarnya seperti makanan, pakaian, dandan, kebersihan diri dan kemandirian ke toilet. Klien adalah putri bungsu dari 2 bersaudara. Anak dengan masalah keterlambatan perkembangan global akan mengalami kesulitan dalam perawatan diri. Klien berusia 4 tahun tinggal bersama orang tua, kakak dan neneknya. Sampai saat ini klien belum dapat berperilaku mandiri dalam aktivitas kesehariannya seperti ke toilet sendiri. Tujuan dari studi kasus ini adalah untuk meningkatkan kemampuan klien untuk mandiri dengan toilet training. Penilaian yang digunakan adalah observasi, wawancara dan VSMS (Vineland Social Maturity Scale). Intervensi yang diberikan untuk meningkatkan kemampuan toilet training klien adalah pemberian penguatan positif. Hasil intervensi yang telah diberikan pada klien menunjukkan perubahan yang signifikan yaitu penurunan intensitas mengompol dan peningkatan kemampuan melepas/memakai celana, mencuci, menyiram dan mencuci tangan secara mandiri. Namun, klien tetap membutuhkan pendampingan keluarga dalam ke toilet atau harus tetap dengan pendampingan dan inisiatif orang tua.